2018
DOI: 10.1177/1757177418789480
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of an infection prevention link nurse programme in community hospitals and development of an implementation model

Abstract: Infection Prevention Background Infection prevention is a global priority, linked to patient safety, the "cornerstone" of healthcare (National Institute for Health and Clinical Excellence, 2012), therefore understanding what works to promote best practice is crucial. Interventions such as education, audit, guidance and feedback have traditionally been used (Storr et al., 2013), often

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Our findings on ICLN' needs for support from various stakeholders builds on the work of Williams and colleagues, who found that ICLN should have access to formal and informal support mechanisms (Williams et al, 2019). The appropriate operationalization of this support is needed to facilitate ICLN to undertake the role (Bunce et al, 2020;Williams et al, 2019).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Our findings on ICLN' needs for support from various stakeholders builds on the work of Williams and colleagues, who found that ICLN should have access to formal and informal support mechanisms (Williams et al, 2019). The appropriate operationalization of this support is needed to facilitate ICLN to undertake the role (Bunce et al, 2020;Williams et al, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…Our findings on ICLN' needs for support from various stakeholders builds on the work of Williams and colleagues, who found that ICLN should have access to formal and informal support mechanisms (Williams et al, 2019). The appropriate operationalization of this support is needed to facilitate ICLN to undertake the role (Bunce et al, 2020;Williams et al, 2019). Therefore, the roles and responsibilities of the ICLN, the team manager, buddies and the infection control practitioner must be defined and balanced at the ward level, with respect to the local culture and power dynamics.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This could be individuals, for example, a clinical champion (Allen et al 2018 ; Becker et al 2020 ), a (clinical) team leader (Anderson & Kynoch 2017 ; Chong et al 2013 ), a project leader (Hu et al 2019 ; Mullins 2021 ; Yu et al 2017 ) or nurse leader (Ceballos et al 2013 ), a nurse clinician (Nazeer et al 2017; Ong et al 2017 ), a knowledge broker (Bayly et al 2018 ), a practice facilitator (Shade et al 2020 ), Facilitator CogChamps (Travers et al 2018 ), a programme or project coordinator (Fleiszer et al 2015 , 2016 ; Monkong et al 2020 ) or an audit team leader (Jia et al 2016 ). In some studies, the leader was the researcher (Mitchell 2017 ) or part of the research team (Kilpatrick et al 2020 ; Rosenberg et al 2016 ; Williams et al 2019 ).…”
Section: Roles Of Nursesmentioning
confidence: 99%